Insulin activates a tyrosine-specific protein kinase in extracts of 3T3-L1 adipocytes and human placenta. - Petruzzelli, L M (1982)
Insulin activates a tyrosine-specific cAMP-independent protein kinase when added directly to detergent extracts of differentiated 3T3-L1 adipocytes and humal placental membranes. The kinase is also activated by antibody to the insulin receptor and, to a lesser extent, by proinsulin. It catalyzes the phosphorylation of the 92,000-dalton component of the insulin receptor, histone, and casein; in each case, tyrosine is the principal amino acid modified. Under the conditions used to activate the kinase, insulin does not affect the rate of dephosphorylation of the receptor or of histone. The insulin-activated kinase is copurified with the human placental insulin receptor until the final elution from insulin-Sepharose. It remains to be established whether the kinase and the insulin receptor are separate molecules.